Perkembangan Kajian Teoritis Tafsir Sosial - Subur Wijaya (LP2M Universitas PTIQ Jakarta, 2017)
This article tries to present an idea of interpretation with a social approach, therefore every problem present may have the same essence, but it may also be a problem that comes then a new issue that demands for immediate response according to the religious understanding derived from the al text -Qur'an. The result is that it is necessary for a mufassir to present a text interpretation capable of addressing current and future social problems. Mufassir should know the various situations and conditions surrounding the dynamics of developing social issues, so that a mufasir (interpreter) can bring the right answer according to the needs of the times as the function of the Qur'an always has the conformity with time and place (i.e., the time of eating).